Syphilis in pregnancy - Samalvides Cuba, Frine (2015)
Syphilis is a sexual transmitted disease caused by Treponema pallidum that compromises multiple systems. It may be acquired or congenital and present in different stages of evolution. The disease has a profound impact on pregnant women and their fetuses’ health, reason for doing universal screening. Clinical manifestations are proteiform depending on the clinical stage; diagnosis is done by non treponemic and treponemic tests. Penicillin is the gold standard in treatment, and desensitizing tests should be performed in allergic patients because alternative drugs have not demonstrated benefit in pregnant women. Follow up is with non treponemic tests and one should expect levels fall four times of its initial value at six months and becoming negative at 12 to 24 months.